Virtuositeit en grootsheid: Aspekte van Hannah Arendt se “buite-morele” etiek van deugdelikheid - Marinus Schoeman (HTS Teologiese Studies/Theological Studies, 2004)
Virtuosity and greatness: Aspects of Hannah Arendt’s “extra-moral” ethic of virtue This article focuses on the “extra-moral” character of Arendt’s view of action and virtuousness. Particular attention is given to her a-teleological, performative (dramaturgical) view of action, which was inspired by the ancient Greeks and Romans, as well as certain aspects of Renaissance humanism, especially Machiavelli’s idea of virtue. According to this view, virtue relates to the virtuosity and “greatness” of the actor’s words and deeds, which in turn presupposes an agonistic ethos where different actors constantly try to surpass one another and to achieve exemplary status. This implies that virtue, or a truly ethical existence, has nothing to do with one’s inner feelings and intentions. Neither can it be measured against some transcendent norm or set of norms. Rather, it manifests itself in the performing of great and virtuosic actions in the presence of others. These actions thus depend on the existence of a vigorous public sphere, while at the same time being co-constitutive of the public sphere, helping to sustain it and keeping it alive. I